Vitamin D and DDX4 regulate the proliferation and invasion of ovarian cancer cells - Chen, Youguo (Oncol Lett, 2018)
Ovarian cancer is one of the most commonly occurring types of cancer and one of the most common causes of cancer-associated mortality in women. Diagnosis of ovarian cancer at an early stage is difficult due to the lack of specific symptoms. In the present study, it is demonstrated that active vitamin D treatment prohibited the proliferation and invasion of ovarian cancer cells, and the expression level of a germ cell specific marker DEAD (Asp-Glu-Ala-Asp)-box helicase 4 (DDX4), which is overexpressed in ovarian cancer, was downregulated by active vitamin D treatment. Knockdown of DDX4 by siRNA could also suppress the invasive ability of ovarian cancer cells. Therefore, DDX4 may be considered as a diagnostic marker of ovarian cancer, and vitamin D may be a candidate drug for ovarian cancer therapy.